Gender and past year serious psychological distress are associated with past year AUD: Time-varying results from the National Survey on Drug Use and Health (NSDUH; 2008–2017). (May 2021) - Verplaetse, Terril L.; Peltier, MacKenzie R.; Roberts, Walter; Pittman, Brian; McKee, Sherry A.
Highlights: Rates of AUD have increased to a greater degree in women vs. men in the last decade. Psychological distress may be related to problematic drinking by gender. Women with psychological distress were over 4 times more likely to have an AUD. Men with psychological distress were 3 times more likely to have an AUD. Psychological distress is an important factor in AUD, particularly in women. Abstract: Background: Rates of alcohol use disorder (AUD) have increased in women in the last decade. Women may be more likely to engage in alcohol use to regulate stress and negative affect compared to men. Findings from our group found that life event stress was more strongly associated with new AUD in women vs. men. Our aim was to extend these findings to psychological distress, a potentially related construct to stress, using a second nationally representative dataset. Methods: Using data from the National Survey on Drug Use and Health (NSDUH; 2008–2017, total n = 562, 072), we examined time-varying associations between gender and past year serious psychological distress (SPD; Kessler-6 distress scale: scores > 13 yes, <13 no) with past year vs. absent DSM-IV AUD. Results: A significant ( p  < 0.0001) gender by SPD interaction for past year vs. absent AUD demonstrated that past year SPD was associated with increased odds of past year AUD in men (OR = 3.33, 95% CI  = 3.15, 3.52) and even greater odds of past year AUD in women (OR = 4.39, 95% CI  = 4.14, 4.66). The gender by SPD by time interaction was not significant ( p  = 0.06). Conclusions: Results highlight that while men with past year SPD were 3 times more likely to have a past year AUD, women with past year SPD were nearly 4.5 times more likely to have a past year AUD. Psychological distress is clearly an important factor in AUD in both men and women, but results suggest that other factors may be driving the increase in rates of AUD in women.